2011
DOI: 10.1021/la2000415
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Surface Wettability via the Modification of Microtextured Titanium Implant Surfaces with Polyelectrolytes

Abstract: Micrometer- and submicrometer-scale surface roughness enhances osteoblast differentiation on titanium (Ti) substrates and increases bone-to-implant contact in vivo. However, the low surface wettability induced by surface roughness can retard initial interactions with the physiological environment. We examined chemical modifications of Ti surfaces [pretreated (PT), Ra ≥ 0.3 μm; sand blasted/acid etched (SLA), Ra ≥ 3.0 μm] in order to modify surface hydrophilicity. We designed coating layers of polyelectrolytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 59 publications
2
46
1
Order By: Relevance
“…21 Interestingly, J. H. Park et al observed and speculated that the incomplete coverage of chitosan, poly(Lglutamic acid) and poly(L-lysine) monolayers on titanium surface is due to the 0.15 M NaCl used to dissolve these polyelectrolytes, which results in the preferential attachment of Na + onto the negatively charged Ti surface. 23 However, this phenomenon is not observed in this study. It can be attributed to the PDA used prior to alginate/chitosan LBL self-assembly.…”
Section: Characterization Of the Alginate/chitosan Lm Construction Pcontrasting
confidence: 64%
“…21 Interestingly, J. H. Park et al observed and speculated that the incomplete coverage of chitosan, poly(Lglutamic acid) and poly(L-lysine) monolayers on titanium surface is due to the 0.15 M NaCl used to dissolve these polyelectrolytes, which results in the preferential attachment of Na + onto the negatively charged Ti surface. 23 However, this phenomenon is not observed in this study. It can be attributed to the PDA used prior to alginate/chitosan LBL self-assembly.…”
Section: Characterization Of the Alginate/chitosan Lm Construction Pcontrasting
confidence: 64%
“…Park et al [65] recently reported that different polyelectrolyte modifications prepared on the native oxide layers of machined and BAE Ti surfaces enhanced the hydrophilicity of the surface without changing its microtopography. Polyelectrolyte coatings shifted the hydrophobicity of the original Ti surfaces to a moderate hydrophilic state with a water CA between 40° and 60°, in contrast to the superhydrophilic modifications described previously ( i.e.…”
Section: Experimental and Marketed Dental Implant Surfaces: Wettinmentioning
confidence: 99%
“…Surface wettability has been modified through several methods including self-assembled monolayers, functional chemical species, multilayers with oppositely charged polymers, and topographical changes [20,21]. We previously demonstrated that surface wettability can be modified by polyelectrolyte coatings applied to sandblasted/acid-etched (SLA) surfaces [4].…”
Section: Introductionmentioning
confidence: 99%